2015
DOI: 10.1590/s0004-28032015000200008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-Alcoholic Fatty Liver Disease in Women With Polycystic Ovary Syndrome and Its Correlation With Metabolic Syndrome

Abstract: -Background -The polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women at childbearing age. Metabolic syndrome is present from 28% to 46% of patients with PCOS. Non-alcoholic fatty liver disease (NAFLD) is considered the hepatic expression of metabolic syndrome. There are few published studies that correlate PCOS and NAFLD.Objective -To determine the prevalence of NAFLD and metabolic syndrome in patients with PCOS, and to verify if there is a correlation between NAFLD and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
3
35
1
Order By: Relevance
“…Furthermore, the relationship between older age and increased prevalence of NAFLD is confirmed in female subjects from the NHANES . However, among the female population, various other factors, including alterations in body composition, fat distribution, hormonal and metabolic changes after menopause, as well as polycystic ovary disease, have been associated with NAFLD . In fact, data suggest that estrogen appears to have a protective role.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the relationship between older age and increased prevalence of NAFLD is confirmed in female subjects from the NHANES . However, among the female population, various other factors, including alterations in body composition, fat distribution, hormonal and metabolic changes after menopause, as well as polycystic ovary disease, have been associated with NAFLD . In fact, data suggest that estrogen appears to have a protective role.…”
Section: Discussionsupporting
confidence: 93%
“…Metabolic syndrome for adults was defined by different criteria, for example 25 articles used the Adult Treatment Panel III (ATP III) and its modifications criteria . Six articles used the American Heart Association/National Heart Lung Blood Institute (AHA) and its modification criteria .…”
Section: Resultsmentioning
confidence: 99%
“…Table presents the assessment of method quality, according to the Newcastle‐Ottawa Scale. Eleven articles achieved scores of seven or more of nine indicating high quality, and six articles achieved score of 5 indicating low quality …”
Section: Resultsmentioning
confidence: 99%
“…Insulin and luteinizing hormone act synergistically, stimulating ovarian theca cells to increase androgen synthesis, inhibiting synthesis of the steroid hormone binding globulin by the liver and increasing the amount of free and biologically active testosterone in circulation. Because IR is the characteristic of MetS, several reports have shown that women with PCOS are more likely to have MetS c[169-171]. Other studies have shown that women with PCOS, regardless of their body weight, have a higher risk for the development of NAFLD.…”
Section: Nonalcoholic Fatty Liver Disease Polycycstic Ovarian Syndromentioning
confidence: 99%
“…Published studies of the coherence between PCOS and NAFLD are still very rare. Further studies are needed to confirm the relationships between these conditions[4,169]. …”
Section: Nonalcoholic Fatty Liver Disease Polycycstic Ovarian Syndromentioning
confidence: 99%